(untitled) (Jurnal Metabio, 2023)
This study aims to determine the effect of the guided inquiry model on students’ conceptual understanding and learning interests. The population in this study were seventh-grade students of SMP Yayasan Perguruan Keluarga Pematangsiantar in the 2021/2022 academic year, consisting of three classes totaling 93 students. The research sample was taken using Cluster Random Sampling, obtaining class VII-2 as the experimental class and VII-3 as the control class, totaling 62 students. The instruments used in the study were questionnaires and tests. The data obtained were analyzed using ANOVA with a significance level of 5% (α = 0.05) using SPSS’21. The results of the hypothesis testing on conceptual understanding ability obtained F count = 15.60, while F table at the 4.001 level. Because F count > F table with a significance value of 0.000 <0.05, Ho is rejected and Ha is accepted. The results of the hypothesis testing on student learning interest obtained F count = 53.11, while F table 4.001. Because F count > F table with a significance value of 0.000 < 0.05, Ho is rejected and Ha is accepted. It was concluded that there is a significant effect of the guided inquiry learning model on students’ conceptual understanding and learning interest in environmental pollution material for seventh-grade students at Yayasan Perguruan Keluarga Pematangsiantar Junior High School in the 2021/2022 academic year.